Analisis Kesulitan Belajar Matematika pada Materi Operasi Hitung Pecahan dan Upaya Menanganinya Untuk Siswa Sekolah Dasar di IV SDN Doyong 2 - Adawiyah, Robiatul; Zuliani, Rizki; Hartantri, Saktian Dwi (MASALIQ, 2021)
This study aims to describe: difficulties in learning mathematics in arithmetic operations material for fourth grade elementary school students at SDN Doyong 2 the factors that cause difficulties in learning mathematics for fourth grade elementary school students and teacher efforts in dealing with learning difficulties experienced by fourth grade students at SDN Doyong 2. This type of research is qualitative research. The informants in this study were fourth grade students and fourth grade teachers at SDN Doyong 2. The data collection techniques used were observation, interviews, test questions and documentation. The data were analyzed through the steps of data reduction, data presentation, and drawing conclusions. The data were analyzed through the steps of data reduction, data presentation, and drawing conclusions. The technique of checking the validity of the data is done by triangulation of sources and techniques.The technique of checking the validity of the data is done by triangulation of sources and techniques. The results of the study show that: 1) the material considered difficult by students is the material for counting fraction operations: difficulty understanding the concept of fractional arithmetic operations distinguishing denominator and numerator, difficulty in solving problems in story problems, difficulty in comparing number symbols, 2) factors that influence students include low interest and motivation in learning mathematics, and the lack of variety or learning methods provided by the teacher, 3) the efforts made by the teacher include providing remedial, using appropriate learning media, providing innovative learning methods, increasing practice questions, and collaborating with parents.